ETR 300 : Optical Centre / Intan Shafeenaz Saad ... [et al.] - Saad, Intan Shafeenaz; Yusop, Nor Fadzilah; Mahmud, Che Rusnani; Marzuki, Nor Akmal; Ahmad, Azila (2001)
We have on the whole agreed and decided to involve ourselves in this world of business which is involves the sales of spectacles, contact lens, and sunglass, computerized eyes testing and also fixing spectales. We got ourselves involved in this form of business, mainly due to the fact that we had high confidence that this business will be very profitable. This is because we feel that is of human nature to always demand for something new. This where we hope that our business will be able to fulfill the needs and wants of the society. Nowadays, most of the optometrist are only involved by non-muslim. So, we as a bumiputra hope that our business can be emulate with non-muslim and increase bumiputra participant in this kind of business. Besides that we also want to improve the quality of eye health vision care among the community surrounding by selling the cheaper goods and affordable reasonable prices. In order to sell in low price, that's why we need to reduce the overhead expenses. Spectacles have many type of frames and lens. Lens, for example there are glass and plastic where plastic more expensive than glass. While the cost of frame mostly depend on where they are made. The frame from Japan and Europe normally expensive than others.